Two of the largest hero stones in the Suswani Mata Temple - Temples of India Project Team (Jio Institute, 2024)
Seen here are two of the largest hero stones found among the fragments in the Suswani Mata Temple. Interestingly, both slabs feature a similar type of depiction where the upper half shows certain human figures while the lower half of the stone slab is empty. The finials of the hero stones are stylized as temple shikharas (superstructures), specifically latina shikharas (mono-spired). Approximately four feet in height and a half foot in width, these hero stones are unique specimens and constitute an important corpus of historical data. The plain portions of the stone slabs have very faint remains of inscriptions, which might contain information about the person in whose honour the hero stone was carved.